Available Major and Micronutrients in Arid Soils of Jamnagar District of Gujarat - Sharma, B K; Kolarkar, A S (Annals of Arid Zone, 2016)
Jamnagar district of Gujarat State, receiving only 250 to 300 mm annual rainfall, falls in the arid climatic region. Twenty seven composite soil samples were collected and analysed for major and micronutrients from the area of this district. Data revealed that these arid soils are poor in organic carbon status, fairly well supplied in available P202and very high in K2O. As regards available Fe, Mn, Zn and Cu, they are found to be adequately supplied and none of the samples is found deficient in any of these nutrients. The Zn and Cu arc found to be significant and positively correlated with organic carbon content. Zn is also found to be positively correlated with CaCO2, while Mn is negatively correlated with it.